Rock physics modeling to evaluate clastic reservoirs: a case study from the Lower Goru Formation, Middle Indus Basin, Pakistan - Hussain, Wakeel; Luo, Miao; Ali, Muhammad; Hussain, Hadi; Ali, Sajid; Iqbal, Jaffar; Nyakilla, Edwin E; Asghar, Ali (Environmental earth sciences, 2024)
The geological factors, including porosity, lithology, and fluid characteristics, control the Rock Physics Models. Several retrospective studies have examined the methods for discriminating and calculating these geologic parameters in the lower Goru Formation sand reservoir. However, there is significant potential that remains unexplored because of inadequate attention to sand distribution. Therefore, this study proposes the development of a Rock Physics Model (RPM) and a Rock Physics Template (RPT) to identify overlooked inadequately consolidated sand reservoirs. Through the analysis of datasets from five wellbores, we built a modified RPM and RPT for the lower Goru Formation clastic reservoir in Pakistan. The evaluation and comparison of RPMs, including stiff-sand, soft-sand, Greenberg, Castagna, and Raymer’s models, aimed to calibrate the ideal model for future researchers. The results indicate that the stiff-sand model is the most suitable RPM. Furthermore, the RPT is used to test the reliability of the predicted results, which is helpful for formation assessment, reservoir delineation, and prospect evaluation across diverse LGF sand reservoir fields. The proposed model facilitates porosity computation based on seismic impedance throughout the LGF in the Indus Basin, Pakistan, and other regions worldwide with similar geologic characteristics and reservoir distributions. The integration of the modified RPM and RPT not only enhances our understanding of the lower Goru Formation clastic reservoir in Pakistan but also provides a framework for future exploration and reservoir management, providing valuable insights applicable to diverse LGF sand reservoirs globally.